Risk Communication During the 2009 A/H1N1 Pandemic– European Stakeholders' Experiences and their Wishes for the Future - Rasmus Cloes (2015)
Objectives: Assess professional stakeholders' (public health officials/health care staff) perceptions in terms of the risk-communication difficulties faced during the different phases of the A/H1N1 pandemic in Europe and their wishes for the future. Methods: Semi-structured interviews were conducted with health professionals involved in the management of the 2009/2010 A/H1N1 pandemic, from different European countries. The interviews were recorded, transcribed, and coded with the software MAXQDA. Results: A total of 25 experts from 8 European countries were interviewed: 9 from the micro-level (nurses and general practitioners), 10 from the meso-level (regional public health experts), and 6 from the macro-level (national public health experts). Analysis of the interviews revealed three main themes: vaccine issues; communication issues; and general problems. As reasons for the low vaccination coverage stakeholders mentioned the late arrival of the vaccines, the moderate character of the pandemic, vaccine safety concerns, and a general skepticism towards vaccination. Communication needs generally did not vary between the European countries, but between the different levels of employment: Macro- and meso-level stakeholders preferred fast information but from multiple sources; the micro-level stakeholders preferred one credible source. Throughout Europe collaboration with the media was perceived as poor and professionals felt misunderstood and misinterpreted. Conclusions: Risk-communication is highly multi-disciplinary; effective riskcommunication requires taking into account the needs of those involved in the process of giving and receiving information. Professional stakeholders should be enabled to access reliable information rapidly through pre-established channels; emphasis should be laid on establishing sustainable co-operations between experts and the media, and measures to improve societies trust in the health authorities, like the transparent communication of uncertainties need to be encouraged.